Correlated ownership: Polanyi, Commons, and the property continuum - Frerichs, Sabine; James, Rick (Research Handbook on the Sociology of International Law, 2018)
According to the economic analysis of law, an efficient property regime is premised on the universality, the exclusivity, and the transferability of property rights. Ideally then, every (legal) person can enjoy the status of an owner and any (economic) resource can become private property; ownership titles could be bought and sold across national jurisdictions and would ultimately be respected everywhere in the world. Throughout history, property regimes indeed seem to have moved towards this ideal. However, this conception of private property is far less natural than it seems, and not without problems. Instead, the institution of property rights is inherently connected with the development of capitalist society, and it reflects the latter’s underlying tensions. The starting point for a sociological account of property rights is to conceive them as a social relation, or a relation of power, which includes (other) owners and non-owners as well as the state as a ‘third party’. In this chapter, the authors build on the work of Karl Polanyi and John R. Commons to suggest that the property regime of the market society relies both on the reification of property (identifying it with the thing owned) and the commodification of the right of ownership (turning it into a marketable commodity). Looking back, the authors retrace how the concept of property changed with the advent of modern capitalism, and how it evolved in the transition from agricultural to industrial capitalism. Looking into the future, they also address the challenges of today’s informational capitalism, which is characterized by the commodification of knowledge. Based on James’s work, the authors introduce the ‘correlative rights doctrine’ as an alternative to the remnant ‘property rights absolutism’ in the field of intellectual property law, but also beyond. With cross-border conflicts in who owns what having proliferated in the global age, investigations into the relational quality of property rights also matter for international lawyers, who are confronted with new subjects and objects of property, from international investment law to intellectual property law.
Law
Keywords: COMMONS; J.R.; international law; property rights

Market Dominance, Crime, and Globalisation - Messner, Steven F.; Rosenfeld, Richard (Social Dynamics of Crime and Control: New Theories for a World in Transition, 2000)
KM: Our point of departure is Karl Polanyi's classic work on the emergence of industrial capitalism and recent studies that further develop Polanyi's insights. We draw on these analyses to pose a fundamental issue confronting all capitalist societies: the need to restrain the market and prevent the economy from dominating other institutional realms. We explain how this general institutional challenge bear specifically on the problem of crime and crime control
Law
Keywords: crime; double movement; globalization; institutional-anomie theory; law

Understanding the (Re-)regulation of Private Renting in England: Karl Polanyi, the Rogue Landlord, the Responsible Tenant and the Decent Home - Carr, Helen; Alcock, Rowan (Contract law and the legislature: Autonomy, expectations, and the making of legal doctrine, 2020)
Law